2009
DOI: 10.5194/acp-9-7257-2009
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Asian aerosols during transpacific transport in INTEX-B

Abstract: Abstract. Measurements of aerosol composition were made with an Aerodyne High Resolution Time-of-Flight Aerosol Mass Spectrometer (HR-ToF-AMS) on board the NSF/NCAR C-130 aircraft as part of the Intercontinental Chemical Transport Experiment Phase B (INTEX-B) field campaign over the Eastern Pacific Ocean. The HR-ToF-AMS measurements of non-refractory submicron aerosol mass are shown to compare well with other aerosol instrumentation in the INTEX-B field study. Two case studies are described for pollution layer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
230
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 192 publications
(263 citation statements)
references
References 176 publications
32
230
1
Order By: Relevance
“…When comparing the time series of total OOA (SV-OOA + LV-OOA) versus O x in Figure 9, similar temporal changes are observed (R 2 = 0.53), but the correlation is stronger during the more polluted periods of high OOA concentrations that occurred in June (R 2 = 0.72 for the 2-6 June high pollution period). It has also been observed that for long-range transported air, the correlation vanishes due to differing losses and ongoing chemistry of SOA and O x [Dunlea et al, 2009]. In Pasadena, the regression slope for OOA versus O x is 0.146(±0.001) μg sm À3 ppbv À1 (Figure 9 inset).…”
Section: Correlation Of Oxygenated Organic Aerosols With the Photochementioning
confidence: 87%
“…When comparing the time series of total OOA (SV-OOA + LV-OOA) versus O x in Figure 9, similar temporal changes are observed (R 2 = 0.53), but the correlation is stronger during the more polluted periods of high OOA concentrations that occurred in June (R 2 = 0.72 for the 2-6 June high pollution period). It has also been observed that for long-range transported air, the correlation vanishes due to differing losses and ongoing chemistry of SOA and O x [Dunlea et al, 2009]. In Pasadena, the regression slope for OOA versus O x is 0.146(±0.001) μg sm À3 ppbv À1 (Figure 9 inset).…”
Section: Correlation Of Oxygenated Organic Aerosols With the Photochementioning
confidence: 87%
“…Thus, cloud processing may enhance the formation of highergeneration SOA tracers at an altitude around 2 km over central China, a point that warrants further study. The observed decreasing trend in the ratios of organic species to sulfate at elevation above 2 km may be explained by less efficient wet removal of SO 2 than those of preexisting aerosols and oxidized VOCs during air mass lifting (Dunlea et al, 2009). The further processing of the resulting air mass may thus lead to the formation of particles relatively enriched with sulfate compared to organics.…”
Section: Vertical Distributions Of Poa and Soa Tracersmentioning
confidence: 99%
“…Factor analysis is not always possible on highly aged organic aerosol datasets. For example, Dunlea et al (2009) found that the limited spectral variability in their measured organic aerosol precluded them from separating it into physically meaningful factors. Here we explore the possible physical meanings of the two OOA factors found for FAME-2008.…”
Section: Positive Matrix Factorizationmentioning
confidence: 99%